1271. In vitro Activities of Ceftaroline and Comparator Agents Against Bacterial Pathogens Frequently Causing Community-Acquired Respiratory Tract Infections in Patients from a Global Population: ATLAS Surveillance Program 2016-2019. (4th December 2021) - Hackel, Meredith; Stone, Gregory; Sahm, Daniel F
Abstract: Background: Community-acquired bacterial pneumonia (CABP) is a frequent cause of patient morbidity and mortality. Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis are frequent etiologic agents of CABP. Ceftaroline fosamil is a parenteral cephem approved for treatment of patients with CABP caused by S. pneumoniae (including cases with concurrent bacteremia), methicillin-susceptible Staphylococcus aureus (MSSA), H. influenzae, and some species of Enterobacterales. In this study we report the in vitro activity of ceftaroline and comparators against isolates from community-acquired respiratory tract infections (CARTI) collected through a global surveillance program. Methods: Clinically relevant, non-duplicate, isolates cultured from respiratory specimens by clinical laboratories in 54 countries in 2016-2019 were collected by the ATLAS Surveillance Program central laboratory (IHMA, Schaumburg, IL, USA). In total, 2, 636 isolates of S. pneumoniae, H. influenzae, M. catarrhalis, MSSA, and methicillin-resistant S. aureus (MRSA) were tested. The isolates (n/percent of total) originated from Asia/South Pacific (722/27.4%); Europe (1481/56.2%); Latin America (292/11.1%); Middle East/Africa (57/2.2%); and North America (Canada only) (84/3.2%). Ceftaroline and comparator agent MICs were determined by CLSI M07 broth microdilution methodology. MICs were interpreted using 2021 CLSI M100 MIC breakpoints. Results: Ceftaroline and comparator agent in vitro activities are summarized in the table. Greater than 98% of S. pneumoniae and >99% of MSSA were susceptible to ceftaroline, including penicillin-nonsusceptible S. pneumoniae based on a dosage of 600 mg every 12h. Sixty-four (24.4%) MRSA were ceftaroline-susceptible-dose-dependent (MIC 2-4 µg/mL) based on a dosage of 600 mg every 8h administered over 2h, with the majority from (n) China (70), S. Korea (19), Japan (10), and Chile (8). Three isolates, all from China, were resistant to CPT (MIC of 8 µg/mL). 99.2% of H. influenzae were susceptible to ceftaroline. Results Table Conclusion: Ceftaroline demonstrated potent in vitro activity against current pathogens associated with CABP from a global collection. Disclosures: Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Gregory Stone, PhD, AztraZeneca (Shareholder, Former Employee)Pfizer, Inc. (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)